2023
DOI: 10.3390/biom13081176
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Oxidative Stress in Manganese Neurotoxicity: A Literature Review Focused on Contributions Made by Professor Michael Aschner

David C. Dorman

Abstract: This literature review focuses on the evidence implicating oxidative stress in the pathogenesis of manganese neurotoxicity. This review is not intended to be a systematic review of the relevant toxicologic literature. Instead, in keeping with the spirit of this special journal issue, this review highlights contributions made by Professor Michael Aschner’s laboratory in this field of study. Over the past two decades, his laboratory has made significant contributions to our scientific understanding of cellular r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 149 publications
0
2
0
Order By: Relevance
“…Manganese deficiency impairs insulin production, causes transient dermatitis, hypocholesterolemia, increased alkaline phosphatases and harmful effects on bone tissue formation. Excessive intake of manganese could lead to neurotoxicity, memory and muscular disorders [ 69 ] . Consumption of 100 g of boiled E. fimriata would cover 27.44% of this RDA.…”
Section: Resultsmentioning
confidence: 99%
“…Manganese deficiency impairs insulin production, causes transient dermatitis, hypocholesterolemia, increased alkaline phosphatases and harmful effects on bone tissue formation. Excessive intake of manganese could lead to neurotoxicity, memory and muscular disorders [ 69 ] . Consumption of 100 g of boiled E. fimriata would cover 27.44% of this RDA.…”
Section: Resultsmentioning
confidence: 99%
“…Several experimental pieces of evidence have suggested that ROS are key regulators of MMP production and that oxidative stress is a primary mechanism of Mn-mediated neurodegeneration [50][51][52][53]. In this study, we investigated whether in Mn-treated rats the increase in MMP levels and expression could be related to an alteration of the redox state in the brain.…”
Section: Discussionmentioning
confidence: 96%